2011
DOI: 10.1016/j.jjcc.2011.03.002
|View full text |Cite
|
Sign up to set email alerts
|

Current status and prospects of antiplatelet therapy in percutaneous coronary intervention in Japan: Focus on adenosine diphosphate receptor inhibitors

Abstract: Dual antiplatelet therapy with aspirin and clopidogrel is routinely used to prevent thrombotic events in patients with acute coronary syndrome undergoing percutaneous coronary intervention (PCI) in Japan. However, these agents have various limitations and some patients will experience further cardiovascular events. The purpose of this article is to review the antiplatelet agents currently used in patients undergoing PCI in Japan, to discuss the issues and limitations associated with these antiplatelet agents, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
10
0
3

Year Published

2012
2012
2017
2017

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 14 publications
(13 citation statements)
references
References 77 publications
0
10
0
3
Order By: Relevance
“…A large number of elderly people with cardiovascular disease, cerebrovascular disease and chronic joint pain have been prescribed low-dose aspirin, antithrombotic drugs, NSAIDs and corticosteroids for primary or secondary prevention of cardiovascular disease, cerebrovascular disorders and arthralgia (18)(19)(20)(21)(22). In the present study, a univariate analysis focused on prescribed medications indicated that low-dose aspirin, antithrombotic drugs and corticosteroids are exacerbating factors for bleeding gastric and/or duodenal ulcers in elderly patients compared with nonelderly patients.…”
Section: Discussionmentioning
confidence: 66%
“…A large number of elderly people with cardiovascular disease, cerebrovascular disease and chronic joint pain have been prescribed low-dose aspirin, antithrombotic drugs, NSAIDs and corticosteroids for primary or secondary prevention of cardiovascular disease, cerebrovascular disorders and arthralgia (18)(19)(20)(21)(22). In the present study, a univariate analysis focused on prescribed medications indicated that low-dose aspirin, antithrombotic drugs and corticosteroids are exacerbating factors for bleeding gastric and/or duodenal ulcers in elderly patients compared with nonelderly patients.…”
Section: Discussionmentioning
confidence: 66%
“…However, PM may not respond to higher doses [31]. An alternative antiplatelet agent, such as prasugrel, may increase the degree of platelet inhibition [32,33]. Large randomized trials have failed to confirm clinical efficacy of tailoring antiplatelet therapy according to results of platelet function tests [34,35].…”
Section: Discussionmentioning
confidence: 99%
“…In Japan, the approved loading dose of clopidogrel is 300 mg and therefore it was the only dose provided to the patients in this registry. 19 Prasugrel and ticagrelor were not approved at the time of this analysis. In were selected for this study, and the study protocol was approved by the institutional review board committee at each site.…”
Section: Methodsmentioning
confidence: 99%